2015
DOI: 10.1007/s00417-015-2929-y
|View full text |Cite
|
Sign up to set email alerts
|

Open-globe injuries with motor vehicle accidents: a 12-year review

Abstract: Fifty-six percent of eyes with an open-globe injury related to MVAs achieved a final VA of 20/200 or better in this series. No eyes developed endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 35 publications
6
12
0
3
Order By: Relevance
“…Considering about gender, the result of this study is consistent with other OGI publications, either investigated for overall causes or only for traffic-related injury, which found that male was a major proportion of patients than female, even though varying in ratio [13,15,16,20,22]. This may refer to differences in physical activities between genders.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Considering about gender, the result of this study is consistent with other OGI publications, either investigated for overall causes or only for traffic-related injury, which found that male was a major proportion of patients than female, even though varying in ratio [13,15,16,20,22]. This may refer to differences in physical activities between genders.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, in road traffic-related OGI, the disparities in age range have been demonstrated. A study in US by Orr et al presented that nearly half of cases (48%) were young patients between 20 to 40 years whereas a study in Japan by Okamoto et al found that road traffic injury comprised a more proportion of elderly patients with a mean age of 50 years [20,22]. This study, similar to Zhang et al, demonstrated that the highest incidence occurred in young patients between 20 to 39 years which represented teenagers and/or early working groups [10].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations